Clinical and radiographic outcomes of replanted avulsed immature permanent teeth: a systematic review - Pratyusha, K Sesha Sai; Chaitanya, Penmatsa; Ahalya, Penmetsa; Vinay, Chandrappa; Ravigna, Peddi; Anusha, Divvi (Brazilian Dental Science, 2025)
Objective: The objective of this systematic review was to evaluate the survival, clinical and radiographic outcomes of replanting an avulsed immature permanent tooth in children. It was intended to address the complications on replanting an avulsed immature permanent tooth irrespective of outcomes. Material and Methods: A comprehensive search was performed using PubMed, Google Scholar, Lilacs and Cochrane databases on 2nd & 3rd November 2024. Titles and abstracts were screened followed by full-text articles from 2000 to 2024. Data extraction was then performed by using a self-designed sheet and risk of bias (ROB) assessment was done using Newcastle-Ottawa Scale. Prospective and retrospective observational studies were included. A total of 3026 articles were screened and eight articles were included in the review. The qualitative synthesis was performed on eight studies. Results: A total of 286 replanted immature avulsed teeth were evaluated. Clinical outcomes included pulpal healing in 31 teeth, pulpal necrosis in 139 teeth, periodontal healing in 50 teeth and apical periodontitis in 22 teeth. Radiographic outcomes included ankylosis-related resorption in 108 teeth, inflammatory-related resorption in 83 teeth, external root resorption in 12 teeth and pulp canal obliteration in 22 teeth. Overall, 97 teeth showed a successful outcome, while 56 teeth were extracted due to poor prognosis. Due to the heterogeneity of the studies, a meta-analysis was not attempted. Conclusion: Evidence suggests that although the survival rate for avulsed teeth was low, replanting immature permanent teeth is essential for future esthetic and functional reconstruction. KEYWORDS Avulsion; Dental trauma; Pulpal necrosis; Replantation; Tooth loss.